Estimating bone loading during physical activity: where do we go next? - Rice, H. (Proceedings of the 10th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2022)
Bone stress injuries affect athletic populations who undertake activities in which bones are repeatedly loaded. In order to understand and reduce the risk of bone stress injuries, we need to quantify the loading experienced by the bones during activities such as running. Bone loading is difficult to quantify as the magnitudes of stress are influenced to a large extent by the magnitude of muscular forces acting on the bone. Musculoskeletal modelling, ranging from very simple to very complex approaches, can be used to estimate the internal loading experienced by the bone during human movement such as running. This has allowed us to explore factors such as speed, slope, step width and step length and their influence on bone loading during running. However, in order to truly understand risk of stress injuries this needs to be taken out of the lab and in-field. Today we have access to rapidly improving technology and data processing capabilities. Could this facilitate the estimation of bo ne loading in real time? What are the current limitations and challenges, and how might these be overcome in the future?